The Impact of ESG on Strategic Success in Jordanian Islamic Banks - Alafi, Khaled Khalaf (International Review of Management and Marketing, 2023)
The study aimed to identify the criteria of ESG with its dimensions (Environmental, Social, and Governance) in Strategic Success with its combined dimensions (Specific Strategy, Specific Implementation, Motivational Culture, and Continuous Innovation). The random sample consists of managers that working in Jordanian Islamic banks with a total of (108) individuals. The study adopted the questionnaire as the study tool and was distributed to the respondents. The questionnaire was developed based on previous studies, and the answers were analyzed using the statistical analysis program (SPSS). The study concluded that there is a high level of implementation of governance pillars and Strategic Success in Jordanian Islamic banks, and that there is a statistically significant impact of all governance pillars represented by (Environmental, Social, and Governance) on Strategic Success. The study recommended that Jordanian Islamic banks must continue to implement governance pillars (ESG) and do more work toward achieving Strategic Success.